Granting Efficacy to the Religious Motives of Terrorists a Reply to Schuurman’s Response to "Bringing Religiosity Back In, Parts I & II" - Dawson, Lorne L. 1954- (2021)
In this reply to Bart Schuurman’s response to my two-part article "Bringing Religiosity Back In: Critical Reflection on the Explanation of Western Homegrown Religious Terrorism," I address how we are speaking at cross-purposes and this leads to misunderstandings. When it comes to discussions of the role of religiosity in motivating jihadist terrorism this situation is common, and hence it is instructive to reexamine how we agree and disagree. Relative to some other prominent scholars, we agree that religiosity can play a role in radicalization and that the level of someone’s religious knowledge is a poor way of determining this on a case-by-case basis. Schuurman implies incorrectly, however, that I treat people’s beliefs as a sufficient explanation for their violent actions. My critique focuses instead on his reliance (with his coauthor John Horgan) on a modern Western privatized conception of religion that reduces the religio-political commitments of Western jihadists to "personal" (i.e., largely psychological) motivations, when religious motivations, which are intrinsically social, play a more independent role in the social ecology of radicalization.
Literaturverzeichnis: Seite 95-96
Keywords: Belief; Extremism; Hofstad Group; Ideology; Religion; Terrorism